2021
DOI: 10.1002/ange.202102807
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Vesicles from Chemically Encoded Lipid‐Grafted Elastin‐like Polypeptides

Abstract: Biomimetic design to afford smart functional biomaterials with exquisite properties represents synthetic challenges and provides unique perspectives. In this context, elastin‐like polypeptides (ELPs) recently became highly attractive building blocks in the development of lipoprotein‐based membranes. In addition to the bioengineered post‐translational modifications of genetically encoded recombinant ELPs developed so far, we report here a simple and versatile method to design biohybrid brush‐like lipid‐grafted‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In this case, the diagram contains a number of additional regimes (ST 1 , ST 2 , CC A 1 , CC A 2 , CC A,B ) that are not present in Figure 6. Dashed lines in regimes ST 2 and ST B indicate the approach to full stretching of the backbones in corona blocks, H = aM A (eqs 43 and 49), which happens when micelles are still starlike. In these regimes, A blocks in the coronae of micelles are laterally compressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the diagram contains a number of additional regimes (ST 1 , ST 2 , CC A 1 , CC A 2 , CC A,B ) that are not present in Figure 6. Dashed lines in regimes ST 2 and ST B indicate the approach to full stretching of the backbones in corona blocks, H = aM A (eqs 43 and 49), which happens when micelles are still starlike. In these regimes, A blocks in the coronae of micelles are laterally compressed.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of δF B to the conformation free energy per chain, 2 indicates that δF B ≫ F, and therefore, aggregation number Q varies according to a different power law dependence at M B ≤ M B *.…”
Section: Starlike Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermosensitive vesicles made of lipidconjugated ELPs using click chemistry have been reported by Ibrahimova et al as a new artificial model of hybrid lipoprotein vesicle membranes. 68 However, to our best knowledge to date, there are only a few reports of utilizing polypeptide-or protein-based vesicle platforms to mimic cell-like functions toward artificial cell development. The future direction in utilizing protein-incorporating, heterogeneous synthetic vesicles through hybridization for artificial cell applications will be discussed in more detail in Section 4.…”
Section: Traditional Homogeneous Syntheticmentioning
confidence: 99%
“…The authors demonstrated the vesicle assembly of recombinant fusion proteins by hybridization with lipids. Moreover, thermosensitive vesicles made of lipid-conjugated ELPs using click chemistry have been reported by Ibrahimova et al as a new artificial model of hybrid lipo-protein vesicle membranes . However, to our best knowledge to date, there are only a few reports of utilizing polypeptide- or protein-based vesicle platforms to mimic cell-like functions toward artificial cell development.…”
Section: Traditional Homogeneous Synthetic Vesicles To Mimic Cell Str...mentioning
confidence: 99%